The Length of the Greater Palatine Canal in a Lebanese Population: a Radio-anatomical Study - Aoun, Georges (Acta Inform Med, 2016)
OBJECTIVE: The aim of this study was to evaluate the length of the greater palatine canal in a Lebanese population using cone-beam computed tomography (CBCT) technology. MATERIAL AND METHODS: In this study, we measured the length of 148 greater palatine canals in 74 CBCT images of Lebanese adult patients (38 females and 36 males). The data obtained was analyzed statistically to determine 1) if age is related to the length of the canal, 2) if the length of the left side tends to be systematically larger or smaller than the length of the right side, and 3) if the mean length of the canals in females is different than the one in males. RESULTS: In a sagittal plane, the average length of the greater palatine canal was 30.62 (30.64 mm on the right and 30.60 mm on the left). CONCLUSION: Within the limits of this study, we concluded that in our sample in a Lebanese population, the length of the greater palatine canal does not significantly vary according to age, gender, and side.